Development of firefighting systems for coastal facilities using water-jet powered fire boats - Abdullin Nail; Khafizov Ildar; Alekseev Dmitriy (E3S Web of Conferences)
The article is devoted to the analysis of fires and their extinguishing at coastal facilities using mobile fire departments to ensure the safety of people, property and the environment. The authors considered effective fire extinguishing using specialized methods and technologies, including the use of fire boats with a water jet engine. The parameters of operation of the pump and hose systems were calculated, the maximum distance from the fire site to the fire and rescue boat and the distribution of forces and means of fire protection units were determined.